Simultaneous tDCS-fMRI Identifies Resting State Networks Correlated with Visual Search Enhancement - Callan, Daniel E.; Falcone, Brian; Wada, Atsushi; Parasuraman, Raja (Frontiers in Human Neuroscience, 2016)
This study uses simultaneous transcranial direct current stimulation tDCS and fMRI to investigate tDCS modulation of resting state activity and connectivity that underlies enhancement in behavioral performance. The experiment consisted of three sessions within the fMRI scanner in which participants conducted a visual search task: Session 1. Pre-training (no performance feedback), Session 2. Training (performance feedback given), Session 3. Post-training (no performance feedback). Resting state activity was recorded during the last five minutes of each session. During the 2nd session one group of participants underwent 1mA tDCS stimulation and another underwent sham stimulation over the right posterior parietal cortex. Resting state spontaneous activity, as measured by fractional amplitude of low frequency fluctuations, for session 2 showed significant differences between the tDCS stim and sham groups in the precuneus. Resting state functional connectivity from the precuneus to the substantia nigra, a subcortical dopaminergic region, was found to correlate with future improvement in visual search task performance for the stim over the sham group during active stimulation in session 2. The after-effect of stimulation on resting state functional connectivity was measured following a post-training experimental session (session 3). The left cerebellum Lobule VIIa Crus I showed performance related enhancement in resting state functional connectivity for the tDCS stim over the sham group. The ability to determine the relationship that the relative strength of resting state functional connectivity for an individual undergoing tDCS has on future enhancement in behavioral performance has wide ranging implications for neuroergonomic as well as therapeutic, and rehabilitative applications.